A Review on Taxol Production through Biotechnological Approaches - M Majidi; AR tarinejad (Institue of Medicinal Plants, ACECR, 2018)
Taxol is a very important anticancer drug which was first isolated from Yew plant (Taxus spp.). However, Taxol supply by extraction from natural sources, has several limitations, and cannot meet current marketchr('39')s demands. Therefore, it seems necessary to use alternative production methods. Producing Taxol through biotechnological approaches is among the main options which have some advantages such as independency of production from geographical and environmental conditions, higher production rate, and ease of extraction. This paper contains a review on some of the most important approaches used in Taxol biotechnological production. The main body of the paper is divided into five main parts: (1) Taxol biosynthesis and related genes, (2) Factors and strategies influencing the production of Taxol by plant cell cultures of Taxus spp., (3) Strategies based on genetic manipulation of Taxus spp. for the production of Taxol, (4) Using heterologous systems in taxane production, and (5) Taxol-producing endophytes and related studies. The current status of utilizing biotechnology in producing Taxol and its future outlooks have been also described.